2011
DOI: 10.1037/a0022950
|View full text |Cite
|
Sign up to set email alerts
|

Cocaethylene formation following ethanol and cocaine administration by different routes.

Abstract: Ethanol alters the hepatic biotransformation of cocaine, resulting in transesterification to a novel active metabolite, cocaethylene. Because of first pass metabolism, oral drug administration might be expected to produce relatively larger concentrations of cocaethylene than would intravenous or smoked administration. We, therefore, compared the effects of route of cocaine administration on the formation and elimination of cocaethylene. Six experienced cocaine users were tested in 6 sessions, approximately 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 35 publications
(56 reference statements)
2
31
0
2
Order By: Relevance
“…The dose of ethanol used in the present study has been reported to elevate heart rate by 5.7 beats/min (Spaak et al, 2008). Similarly, combining ethanol with cocaine has been shown to significantly elevate heart rate in humans compared with cocaine alone (Herbst et al, 2011).…”
supporting
confidence: 51%
See 2 more Smart Citations
“…The dose of ethanol used in the present study has been reported to elevate heart rate by 5.7 beats/min (Spaak et al, 2008). Similarly, combining ethanol with cocaine has been shown to significantly elevate heart rate in humans compared with cocaine alone (Herbst et al, 2011).…”
supporting
confidence: 51%
“…3). In an analogous fashion, ethanol has been reported to elevate cocaine exposure (Perez-Reyes, 1994;Farre et al, 1997) while serving as a transesterification substrate yielding CES1-mediated cocaethylene in humans (Herbst et al, 2011) and in other species (Roberts et al, 1993;Hedaya and Pan, 1996;Parker and Laizure, 2010). The significant elevation of heart rate upon combining ethanol with either dl-MPH or d-MPH (Fig.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…When both ethanol and cocaine are present in the liver, the enzyme carboxylesterase-2 catalyzes a transesterification of the methyl ester moiety to an ethyl ester to produce the psychoactive metabolite cocaethylene [6]. In humans who ingest alcohol, between 18% and 34% of cocaine is metabolized to cocaethylene [7]. Like cocaine, cocaethylene has been shown to rapidly enter the brain where it blocks the dopamine transporter and prevents dopamine reuptake.…”
Section: Introductionmentioning
confidence: 99%
“…With alcohol co-administration, ~24% (intravenous), ~34% (oral), or ~18% (smoked) of cocaine is converted to cocaethylene through transesterification. [18] Hence, a truly valuable mutant of human BChE for anti-cocaine enzyme therapy development should be efficient for not only cocaine, but also norcocaine and cocaethylene.…”
Section: Introductionmentioning
confidence: 99%